(untitled) (Archaeologia Adriatica, 2008)
An aes grave (Inventory no. AMS 5224; weighing 327.14 g) of the Apollo/Apollo type (RRC 18/1) is kept in the collections of the Archaeological Museum in Split. It belongs to the issue of Rome, dated between 275 - 270 BC. It was found around 1901, at Jesenice. The context in which it was found provides no information about the find. Jesenice is a village at an altitude of about 200 to 250 m, on the slope of Perun – on the southern side of Mosor Mountain. Apart from other Hellenistic finds in the Jesenice area, along the coastline between Split and Omiš, this find could offer evidence for links of the Illyrians and Greeks from Issa and Pharos, via the nearby Epetion (Stobreč), i.e. with the first Roman traders who must have been in contact with the Illyrians through of Greek colonies. Along with the aes grave from Jesenice, the collections of the Archaeological Museum in Split house another three semisses. There are two (Inventory no. AMS 3255, weighing 145.58 g, and no. AMS 3257, weighing 119.82 g) of the bull/wheel type (RRC 24/4), issued from 265-242 BC, and one (Inventory no. AMS 3256, weighing 125.90 g) of the Saturn/prow type (RRC 35/2), issue date 225-217 BC. Such early Roman coins did not serve as money in the Illyrian area. The aes grave from Jesenice was, most probably, considered simply to be an object made of bronze, precious and outstanding, and was therefore stored as such, and not used for the manufacture of other bronze objects.